A Review on the Mechanism of Reservoir-Induced Seismicity for Nepalese Context - Joshi, Umesh Raj; Maskey, Ramesh Kumar; Kafle, Kumud Raj (Nepal Journal of Science and Technology, 2020)
Over 90 cases of Reservoir Induced Seismicity have been recorded around the earth. The magnitude was varying from 3.0 to 6.3 on the Richter scale. A Reservoir Induced Seismicity (RIS) can increase the frequency of earthquakes in seismically active zones and cause a shock in seismically inactive zones. Nepal is situated in a seismically active zone with six large earthquakes of magnitude equal to or greater than 7.6. It increases the risk of RIS, while several storage-type hydropower projects are being proposed in Nepal. Seismic activities recorded around the Kulekhani-I reservoir could be a reservoir induced seismicity. However, consistent data of seismic events and reservoir levels during all phases of filling or drawing of water level is missing. This paper reviews the researches on seismic activities caused by reservoirs or tectonic movements, and the need for the study on the mechanism of RIS for the Nepalese context is identified.